The effects of perceived social support on postpartum depression - Taştan, Kenan; Demiröz, Halime Pınar (Journal of Surgery and Medicine, 2018)
Aim: Links between pregnancy and depression, especially during the first postpartum months are well recognized. Pregnancy-related depression may harm the mother as well as her baby. We aimed to investigate the effects of social support on depression in mothers during the postpartum period. Methods: A cross-sectional study was conducted in Erzurum city center involving 110 mothers. Data was collected using The Edinburgh Postpartum Depression Scale (EPDS) and Multidimensional Scale of Perceived Social Support (MSPSS). Results: Mean age of the participants was 28.8±5.9 years. Majority of the participants were housewives (75.5%; n=83). Of the participants, 26.4% (n=29) reported of having depression history. According to the EPDS, 47.3% of the mothers (n=52) had scores above the cutoff. The mean EPDS and MSPSS scores were 12.0±4.7 and 58.3±13.0, respectively. There was a significant negative correlation between the EPDS and the MSPSS scores (r=-0.42; p<0.001) Conclusion: Social support and postpartum depression are firmly connected. Effective screening methods and early detection of postpartum depression should be utilized in connection with the primary healthcare providers, especially in areas with high risk, to prevent harmful effects of postpartum depression on maternal, infant and family health.